Research Progress of Methods of Initial Water Rights Allocation in River Basins - WU Dan; LIU Mengyao (Renmin Zhujiang)
The development of a robust and highly feasible method of initial water rights allocation in a river basin can provide important support for promoting high-quality economic development of the river basin and optimizing the layout of its industrial structure.This paper systematically reviews the methods of initial water rights allocation in river basins from four aspects:multi-objective coupling allocation methods,multi-stage coupling allocation methods with stakeholder participation,allocation methods oriented towards industrial structure optimization,and adaptive allocation methods.The results show that multi-objective coupling allocation methods focus on the coordinated reflection of multi-dimensional objectives,such as social equity,economic benefits,ecological protection,and risk control.The multi-stage coupling allocation methods with stakeholder participation concentrate on strengthening the interest interaction among water resource stakeholders and fully reflecting their interest demands.The allocation methods oriented towards industrial structure optimization center on promoting the optimization and upgrading of the industrial structures in river basins.The adaptive allocation methods highlight the improvement of the adaptability of the water resources in river basins to economic and social development.Initial water rights allocation in river basins has gradually developed from "multi-objective coupling allocation methods based on allocation principles" to "adaptive allocation methods based on allocation principles and the negotiation game mechanism".Solving the problem of adapting initial water rights to industrial structure optimization and promoting the optimization and upgrading of industrial structures and high-quality economic development will become the main lines of research on initial water rights allocation in river basins in the future.